Checkers game app - Sharan, Smita (Kansas State University, 2016)
Android Phones and Tablets are driven by apps and becoming more and more popular these days. Enthusiastic game players around the world are always looking for fun and exciting games which are easily accessible from their handheld devices like smartphones, tablets etc. Checkers is one such mobile game app based on the popular game American Checkers or Draughts and is developed on Android platform. This game is turn based in which players play against each other. The player capture the pieces of opponent and progresses diagonally, trying to become the winner by capturing all the pieces of opponent or blocking the opponent so that there is no legal moves left. There are various features in the game. Instant messaging allows players to chat during the game.. Saved Games feature lets users to play the incomplete games later. Leaderboards and Scores make the game competitive as players can see their rankings and scores after the game. Tournaments and Scheduling enables players to schedule matches. Tournament is scheduled with Round Robin process wherein each player plays with all other players in turn and finally winner is declared after end of the game.
Keywords: Checkers; Android; App; Game